A Computerized Physician Order Entry Set Designed to Improve Safety of Intravenous Haloperidol Utilization: A Retrospective Study in Agitated Hospitalized Patients - Muzyk, Andrew J.; Rivelli, Sarah K.; Jiang, Wei; Heinz, Heather; Rayfield, Amber; Gagliardi, Jane P. (Drug safety, 2012)
Background: Intravenous haloperidol can increase the risk for corrected QT (QTc) interval prolongation, torsades de pointes (TdP) and sudden death. Objective: The purpose of this study was to examine the effects of implementation of a computerized physician order entry (CPOE) set on adherence to monitoring parameters, maximum and cumulative doses, and identification or mitigation of risk factors for QTc prolongation in patients prescribed intravenous haloperidol. Methods: A retrospective cohort study of medically ill hospitalized inpatients prescribed intravenous haloperidol was conducted. Data were collected for two distinct 1-year time periods: the pre-CPOE set period (30 June 2007 through 30 June 2008) and the post-CPOE set period (1 January 2009 through 1 January 2010). The CPOE set was implemented on 1 October 2008. Results: A total of 151 subjects were included; 84 subjects were in the pre-CPOE set group and 67 subjects were in the post-CPOE set group. Following CPOE set implementation, subjects in the post-CPOE group, compared with the pre-CPOE group, were more likely to receive a 24-hour cumulative dose of intravenous haloperidol <2mg (Fisher’s exact test; p< 0.048), have a baseline ECG (Fisher’s exact test; p = 0.045), have a follow-up ECG within 24 hours of intravenous haloperidol administration (Fisher’s exact test; p = 0.009) and have a magnesium value assessed at the time of intravenous haloperidol administration (Fisher’s exact test; p = 0.004). Conclusion: This study reports on the successful implementation of a CPOE set designed to improve the safety of intravenous haloperidol administration in medically ill patients.